2012
DOI: 10.1007/s00467-012-2308-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin E or vitamin A on the prevention of renal scarring in children with acute pyelonephritis

Abstract: Vitamins A or E supplements were effective in reducing renal scarring secondary to acute pyelonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…Four studies [25][26][27][28] investigated the effect of vitamin A administration on renal damage in children after APN, with a total of 248 patients aged 1-144 months (120 in the experimental group and 128 in the control group). Three studies [25][26][27] were performed in Iran and one [28] was performed in China. Vitamin A was administered in addition to antibiotic therapy in the experimental group, either orally or intramuscularly.…”
Section: Characteristics Of Studies Included In the Final Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [25][26][27][28] investigated the effect of vitamin A administration on renal damage in children after APN, with a total of 248 patients aged 1-144 months (120 in the experimental group and 128 in the control group). Three studies [25][26][27] were performed in Iran and one [28] was performed in China. Vitamin A was administered in addition to antibiotic therapy in the experimental group, either orally or intramuscularly.…”
Section: Characteristics Of Studies Included In the Final Analysismentioning
confidence: 99%
“…The remaining four RCTs [25][26][27][28] were included in the final meta-analysis. The study by Sobouti et al [27] investigated the effect of vitamins A or E on renal damage, reported the numbers of kidney units with renal damage as outcome of interest and had three arms, with the third arm investigating the benefit of adding vitamin E. Only the two arms exploring vitamin A use on renal damage when compared with the control group were included in this systematic review.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Due to significant interest in the strong antioxidant function, low toxicity, and rare side effects of vitamin E, investigations on the application of vitamin E against kidney diseases have primarily concentrated on clinical studies in recent years [31,32,59]. However, to establish vitamin E as an important ally for human health, particularly in AKI protection, it is necessary to empirically resolve an appropriate therapy mode as well as appropriate dosage.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Our previous study showed the rate of renal parenchymal scars after fi rst episode of acute pyelonephritis to be about 42% (1). The prevalence of renal scars in hypertensive children is 21% (2).…”
Section: Introductionmentioning
confidence: 98%